Are we explaining the movement of hotel room rates correctly? - Lee, Chew Ging (2020)
Demand function, inverse demand function or market equilibrium condition has been used to estimate the empirical models that explain the movement of hotel room rates. However, hotels generally face excess supply of rooms. This research paper develops a simple theoretical model to link hotel room rates to excess supply of hotel rooms. The annual data of Singapore from 1991 to 2017 is used to test this framework. Due to small sample size, with only 27 observations, the bounds testing approach to cointegration is applied on the annual data of hotel industry in Singapore because the obtained estimators are super-consistent. It is found that average hotel room rate and average hotel occupancy rate are cointegrated to confirm hotel room rates and excess supply of hotel rooms are inversely correlated. In order to avoid model mis-specification, major crises are captured by dummy variables which are treated as fixed regressors in the bounds testing approach to cointegration. The empirical and theoretical frameworks used in this study suggest that when hotel occupancy rate is used as an independent variable in modelling the determination of hotel room rates, a researcher is adopting excess supply framework developed in this paper. Furthermore, this framework teaches students in tourism a simplified way to explain the movement of hotel room rates, while still reminding students about the complexity of hotel industry.
Bibliografija: str. 32-33.
Summary.
Keywords: Hoteli -- Cijene usluga -- Ponuda -- Kointegracija; Singapur